The Effect of Waste Flex Banner Fiber on Mechanical Properties of Geopolymer Concrete - Maulana, Farhan; Setiawan, Agustinus Agus (Universitas Ibn Khaldun, 2025)
This research aims to design a geopolymer concrete mix with the addition of waste flex banner fiber and to study its effects on various physical and mechanical properties of the concrete. The study focuses on the influence of flex banner fiber on the density of geopolymer concrete, workability with a target slump value of 90 mm, and the compressive and splitting tensile strength with flex banner fiber additions of 0.5%, 0.75%, and 1.0% by weight of fly ash. The research method involves curing the concrete in water for 7, 14, and 28 days. The results indicate that the addition of flex banner fiber increases the density of geopolymer concrete, achieving an optimal density of 2462.83 kg/m³. This study also shows that the workability of the flex banner fiber mix in geopolymer concrete meets the target slump value of 90 mm at a 0.75% fiber addition. As the fiber percentage increases, a significant reduction in slump value occurs. At 0.5% fiber content, the slump value decreases to 110 mm, while at 1% fiber content, the slump value drops to 53 mm. The addition of flex banner fiber improves the mechanical properties of geopolymer concrete. The compressive strength of geopolymer concrete with 0.75% fiber addition increases by 4.19%. Furthermore, the optimal splitting tensile strength is achieved with a 0.61% flex banner fiber addition.